Analysis of structural brain asymmetries in attention‐deficit/hyperactivity disorder in 39 datasets. (22nd March 2021) - Postema, Merel C.; Hoogman, Martine; Ambrosino, Sara; Asherson, Philip; Banaschewski, Tobias; Bandeira, Cibele E.; Baranov, Alexandr; Bau, Claiton H.D.; Baumeister, Sarah; Baur‐Streubel, Ramona; Bellgrove, Mark A.; Biederman, Joseph; et al.
Abstract : Objective: Some studies have suggested alterations of structural brain asymmetry in attention‐deficit/hyperactivity disorder (ADHD), but findings have been contradictory and based on small samples. Here, we performed the largest ever analysis of brain left‐right asymmetry in ADHD, using 39 datasets of the ENIGMA consortium. Methods: We analyzed asymmetry of subcortical and cerebral cortical structures in up to 1, 933 people with ADHD and 1, 829 unaffected controls. Asymmetry Indexes (AIs) were calculated per participant for each bilaterally paired measure, and linear mixed effects modeling was applied separately in children, adolescents, adults, and the total sample, to test exhaustively for potential associations of ADHD with structural brain asymmetries. Results: There was no evidence for altered caudate nucleus asymmetry in ADHD, in contrast to prior literature. In children, there was less rightward asymmetry of the total hemispheric surface area compared to controls ( t  = 2.1, p  = .04). Lower rightward asymmetry of medial orbitofrontal cortex surface area in ADHD ( t  = 2.7, p  = .01) was similar to a recent finding for autism spectrum disorder. There were also some differences in cortical thickness asymmetry across age groups. In adults with ADHD, globus pallidus asymmetry was altered compared to those without ADHD. However, all effects were small (Cohen's d from −0.18 to 0.18) and would not survive study‐wide correction for multiple testing. Conclusion: Prior studies of altered structural brain asymmetry in ADHD were likely underpowered to detect the small effects reported here. Altered structural asymmetry is unlikely to provide a useful biomarker for ADHD, but may provide neurobiological insights into the trait.